2014
DOI: 10.2478/jwld-2014-0007
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of shallow foundation design using Eurocode 7 and Polish Standard

Abstract: Bearing capacity of cohesive soils was calculated based on PN-B-03020:1981P and Eurocode 7. Strength parameters of cohesive soil modified by the authors: shear strength in undrained conditions c u , effective cohesion c' and effective friction angle φ' were adopted for calculations acc. to Eurocode 7. Values of these parameters depend on a leading parameter -liquidity index I L .Bearing capacity was calculated for two pad foundations of a size B × L = 2.0 × 3.0 m and 1.5 × 2.0 m and for one 2.0 × 14.0 m strip … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In geotechnical structure the analysis of dimensioning and tolerances were developed by Hillyard and Braid (1978) and other workers as Light and Gossard (1983) had applied new methods to modify a part of geometry. The researcher Olchawa and Zawalski (2014) had found that certain values of coefficients obtained by using Eurocode 7 are higher than those prescribed in the design of shallow foundations. In accordance with the structural tolerance, some specific errors of dimensioning were detected by Zong and Mao (2015) through analysis and mathematical modeling.…”
Section: Introductionmentioning
confidence: 99%
“…In geotechnical structure the analysis of dimensioning and tolerances were developed by Hillyard and Braid (1978) and other workers as Light and Gossard (1983) had applied new methods to modify a part of geometry. The researcher Olchawa and Zawalski (2014) had found that certain values of coefficients obtained by using Eurocode 7 are higher than those prescribed in the design of shallow foundations. In accordance with the structural tolerance, some specific errors of dimensioning were detected by Zong and Mao (2015) through analysis and mathematical modeling.…”
Section: Introductionmentioning
confidence: 99%